Hand gesture recognition using ensemble method - Kowsar, Sahib; Chowdhury, Mahzabin; Mahmud, MD Safin; Haque, Shahbaj Shafin; Shifa, Asaka Akther (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.